Study on Environmental Perception of Visitors in Tijuca National Park (Research, Society and Development, 2020)
The objective of this study was to investigate the profile of visitors to the Tijuca National Park (TNP) as well as to analyze the perception they have about Park management and infrastructure related aspects such as installation of information plates, waste baskets, security and surveillance. In addition, it was intended to identify the agreement of the visitors in relation to the level of impacts from some anthropic actions, such as the use of grills and picnics in the perimeter of the NWP. To that end, questionnaires were applied in the form of an online form to 99 visitors from May 22 to June 15, 2019. Regarding the composition of these questionnaires, the authors used questions about the visitor's profile, there were open questions with the intention of analyzing the environmental perception of the people who attend the Park and closed questions, about infrastructure and activities developed in the PNT, using the Likert scale (agreement and importance). From the analysis of the data, it was possible to perceive that the majority of the visitors belonged to the female gender, older than 40 years and that the location of the Tijuca National Park favored the dynamics of visitation. In addition, it was found that waste baskets, while important, needed to be implemented strategically to minimize possible damage to the local ecosystem and that practices such as barbecues should not be undertaken in the Park area. With the research it was possible to reach satisfactory results on the questions proposed in the study, serving as a basis for future conservation studies in the TNP.